A combined model with optimal solution for prediction of grinding temperature. (1st January 2014) - Zhu, Dahu; Li, Beizhi; Ding, Han
The purpose of this study is to experimentally verify whether it is appropriate just substituting energy partition values from one model into other temperature model to calculate the grinding temperature. Two energy partition models (Guo's ε model and Jin's ε model) and three temperature rise models (Guo's T model, Jin's T model and Li's T model) are used for combinations to determine the optimal solution of grinding temperature. The effects of the combined models are explored for three kinds of workpiece materials (Ti-6Al-4V, AISI5140 and SiC) by dry and wet grinding. It has been found that the combinations of Li's T model and either Guo's or Jin's ε model can obtain the optimal solutions, of which the combination of Jin's ε model and either its corresponding T model or Li's T model is more suitable for dry grinding, and the combination of Guo's ε model and Li's T model can be largely used for calculating temperature in wet grinding. The theoretical results also indicate that the grinding temperature is sensitive to the deviation of the thermal properties of composite solid.